Mise à jour de la fiche signalétique de l’Écosse - Jean Berton (Revue Française de Civilisation Britannique)
The theme of updating Scotland’s documents developed in this article is centred on three points: the names and portraits of the nation, how valid the state of the union with England can be today (when compared to how powerful the idea of marriage was in the 16th century), and how Scots and Gaelic have managed to survive the invasion of English. Since Britannia, Scotia and Caledonia are part of the Roman heritage, one must be prepared to be familiar with Scotland’s history so as to evaluate the age-old antagonism between England and Scotland and the survival of the nation’s indigenous languages.